First‐Trimester Nonvisualization of the Parotid Gland and Aneuploidy in Fetuses With Increased Nuchal Translucency: A Prospective Cohort Study. (17th June 2020) - Perlman, Sharon; Sukenik‐Helevy, Rivka; Odeh, Marwan; Keren Gilat, Efrat; Gilboa, Yinon
Abstract : Objectives: Aplasia and hypoplasia of the major salivary glands, particularly the parotid glands, were reported to be associated with trisomy 21. This study aimed to evaluate the value of first‐trimester nonvisualization of the parotid gland in a high‐risk population of fetuses with increased nuchal translucency (NT). Methods: A single‐center prospective observational cohort study was conducted. The feasibility of imaging the parotid gland was assessed in 100 sequential cases of routine low‐risk NT scans. In a 2‐dimensional image in an axial plane at the level of the fetal mandible, the parotid glands appear as bilateral hyperechoic round areas. Cases referred for counseling for an NT measured above the 95th percentile for gestational age were evaluated for visualization of the parotid glands. Prenatal findings were correlated with fetal genetic analysis results. Results: Forty‐two cases with increased NT constituted the final study group. Within the group with nonvisualization of the parotid gland, genetic testing revealed 9 cases of trisomy 21, 3 cases of trisomy 18, and 1 case of monosomy X. The sensitivity and specificity of nonvisualization of the parotid gland as a predictor of aneuploidy were 76% and 80%, respectively. The positive likelihood ratio, negative likelihood ratio, and relative risk were 3.82 (95% confidence interval [CI], 1.67–8.74), 0.29 (95% CI, 0.12–0.71), and 4.33 (95% CI, 1.69–11.09; P  < .01). The negative predictive value was 95.14%. Conclusions: First‐trimester nonvisualization of the parotid gland may constitute a potential method for detection of aneuploid fetuses within a high‐risk population.